2019
DOI: 10.1186/s13756-019-0478-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of antibiotic prescribing behaviors of primary care physicians in Hubei of China: a structural equation model based on the theory of planned behavior

Abstract: BackgroundOver-prescription of antibiotics is prevalent all over the world, contributing to the development of antibiotic resistance. The importance of understanding how physicians prescribe antibiotics is increasingly highlighted for the purpose of promoting good practice. This study aimed to identify factors that shape the antibiotic prescribing behaviors of physicians in primary care based on the theory of planned behavior (TPB).MethodsData were collected from 503 prescribers within 65 primary care faciliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 38 publications
8
37
0
Order By: Relevance
“…Consistent with previous research [42][43][44], attitude and perceived behavioral control are the important in uencing factors of health professionals' intention to use a certain service or product. TPB suggests that an individual's intention and usage behavior are the results of internal factors, the consistency of behavior with attitude and motivation is the requirement of performing a speci c behavior [45].…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous research [42][43][44], attitude and perceived behavioral control are the important in uencing factors of health professionals' intention to use a certain service or product. TPB suggests that an individual's intention and usage behavior are the results of internal factors, the consistency of behavior with attitude and motivation is the requirement of performing a speci c behavior [45].…”
Section: Discussionsupporting
confidence: 86%
“…Secondly, we observed the changes in the percentage of patients receiving antibiotics. The PRA and PRCA indices, which are used by the Chinese government to evaluate the effects of clinical application management of antibacterial therapeutics (National Health Commission of the People's Republic of China, 2015b), were also used by scholars to analyze prescribing practice (Yang et al, 2014;Liu et al, 2019). In this study, the PRA and PRCA presented a decreasing trend and reduced levels after intervention.…”
Section: Discussionmentioning
confidence: 94%
“… 10–15 For example, Liu et al noted that rational prescribing practices are prone to weak control over prescribing behaviours, and 40% of prescriptions in a primary care setting in Hubei, China, contained an antibiotic, with 10% containing two or more antibiotics. 14 Where antibiotic stewardship efforts have worked, they have relied on dedicated committees overseeing antibiotic use, prompt laboratory investigations, established guidelines for empiric prescribing and an easily accessible antibiogram. 16 However, none of these components of an antibiotic stewardship strategy were in place in the four countries included in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Previous studies from low-and-middle-income countries (LMICs) have reported that patient demands often play a salient role in inconsistent prescription practices. [10][11][12][13][14][15] For example, Liu et al noted that rational prescribing practices are prone to weak control over prescribing behaviours, and 40% of prescriptions in a primary care setting in Hubei, China, contained an antibiotic, with 10% containing two or more antibiotics. 14 Where antibiotic stewardship efforts have worked, they have relied on dedicated committees overseeing antibiotic use, prompt laboratory investigations, established guidelines for empiric prescribing and an easily accessible antibiogram.…”
Section: Incomplete Intake Of Antibiotic Treatment and Explanatory Famentioning
confidence: 99%